PT. RAVISHANKAR SHUKLA’S CONTRIBUTION TO THE NATIONAL MOVEMENT - Shukla, Pradeep (International Journal of Research -GRANTHAALAYAH, 2017)
It is rare to see a person who possesses many qualities of a person at the same time. Late Pt. Ravishankar Shukla, the leader of the masses of the old Madhya Pradesh and the new Madhya Pradesh, was one such rare person. In the freedom struggle, while he fought like a firm and determined soldier, firm on his principles, he felt a deep sense of compassion, love and sympathy in his heart when he saw the backward and poor people of his state. After independence, as soon as he came into the administrative field, he started serving his beloved people and continued doing this till his last breath.